2010
DOI: 10.1057/dddmp.2010.6
|View full text |Cite
|
Sign up to set email alerts
|

Minimum effective frequency for interactive television ads

Abstract: A key task for advertising media planners is setting a frequency goal for a campaign. This study used a controlled experiment to identify the minimum effective frequency (MEF) for TV ads offering interactive response, as opposed to direct response by phone call. Participants ( N = 273) were exposed to ads one, three or fi ve times. A control cell saw normal TV ads, while an interactive TV (iTV) cell saw the same ads with interactive response banners superimposed. We found the usual ' build-up ' effects for rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A higher number of stock touts published also extends the reach of the corresponding campaign, especially when these recommendations are sent by different promoters who are followed by different groups of investors. In the context of advertising, extending a campaign's reach has proven to foster advertising success (Bellman, Schweda, & Varan, ). A pump and dump campaign can be assumed to profit from a higher number of promoters as well.…”
Section: Background and Research Hypothesesmentioning
confidence: 99%
“…A higher number of stock touts published also extends the reach of the corresponding campaign, especially when these recommendations are sent by different promoters who are followed by different groups of investors. In the context of advertising, extending a campaign's reach has proven to foster advertising success (Bellman, Schweda, & Varan, ). A pump and dump campaign can be assumed to profit from a higher number of promoters as well.…”
Section: Background and Research Hypothesesmentioning
confidence: 99%
“…Media planners have always been interested in scheduling advertising in a way that achieves the greatest possible outcome per dollar spend (Bellman et al , 2010; Broussard, 2000). In advertising, the term “effective frequency” is used to describe the number of times a consumer must be exposed to an advertising message before the marketer achieves the desired response; whether that be remembering the brand, enhancing the attitude, or buying the product.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time they come with the limitation of presenting the advertisements in a somewhat artificial setting. Nevertheless, former research [33,34] showed that even one-time exposure to advertisements in an experiment can be predictive of real life, in-market effects and an effective way to test the cause and effect relationships described in our hypotheses.…”
Section: Methodsmentioning
confidence: 88%
“…Although previous research [33,34] showed that even one-time exposures in a controlled environment can be predictive of in-market effects in real life people, additional testing in a more natural environment is advised to validate the cause and effect relationships found in our controlled experiments. In real life, people are usually exposed to advertisements for a much shorter time.…”
Section: Limitations and Further Researchmentioning
confidence: 98%